South African dust contribution to the high southern latitudes and East Antarctica during interglacial stages - Gili, Stefania; Vanderstraeten, Aubry; Chaput, Amélie; King, James; Gaiero, Diego Marcelo; Delmonte, Barbara; Vallelonga, Paul; Formenti, Paola; Di Biagio, Claudia; Cazanau, Mathieu; Pangui, Edouard; Doussin, Jean François; et al. (Communications Earth & Environment)
Mineral dust is a natural tracer of atmospheric composition and climate variability. Yet, there is still much to be known about the Southern Hemisphere dust cycle. Major efforts have attempted to solve the puzzle of the origin of the potential source areas contributing dust to the Southern Ocean and East Antarctica. Here we present a comprehensive geochemical characterization of a source area, whose role as a dust supplier to high latitude environments has significantly been underestimated. Sediments collected within the major dust-producing areas along the Namibian coast in Southern Africa (Kuiseb, Omaruru and Huab river catchments and the Namib Sand Sea region), were analyzed for radiogenic isotope ratios and rare earth element concentrations. We find that during warm periods, the Southern African dust signature can be found in archives of the Southern Hemisphere, especially in the Atlantic sector of the Southern Ocean and peripheral areas of the East Antarctic plateau. Fil: Gili, Stefania. Université Libre de Bruxelles; Bélgica. University of Princeton; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Vanderstraeten, Aubry. Université Libre de Bruxelles; Bélgica Fil: Chaput, Amélie. University of Montreal; Canadá Fil: King, James. University of Montreal; Canadá Fil: Gaiero, Diego Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Delmonte, Barbara. Università degli Studi di Milano; Italia Fil: Vallelonga, Paul. University of Western Australia; Australia ...